1984
DOI: 10.1212/wnl.34.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Alzheimer's disease, and the cholinergic system of the basal forebrain

Abstract: All giant neurons of the medial basal forebrain stained for choline acetyltransferase (ChAT). Cell numbers declined from 400,000 to 475,000 in young controls to approximately 140,000 in elderly controls. Five senile dementia cases had counts ranging from 45,000 to 100,000 cells. ChAT levels in control frontal cortex decreased from 1.2 mumol/hr/100 mg protein at age 40 to 0.5 at age 95. Five senile dementia cases had levels ranging from 0.04 to 0.30. When the cholinergic cell count in the basal forebrain drops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
129
1
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(145 citation statements)
references
References 0 publications
13
129
1
2
Order By: Relevance
“…The hypersensitivity to scopolamine, which has been demonstrated in elderly participants when compared to younger participants (Flicker et al, 1992;Ray et al, 1992;Zemishlany and Thorne, 1991) and in participants with AD when compared to non-demented elderly participants (Sunderland et al, 1987), is consistent with the well-established age-and AD-related changes in a number of markers, including reductions in the size and number of cholinergic neurons in the NBM (McGeer et al, 1984;Whitehouse et al, 1982). Thus, the increased cognitive toxicity to trihexyphenidyl that we observed in participants with the APOE-e4 allele may reflect some form of decreased cholinergic function or reserve in this population.…”
Section: Discussionsupporting
confidence: 70%
“…The hypersensitivity to scopolamine, which has been demonstrated in elderly participants when compared to younger participants (Flicker et al, 1992;Ray et al, 1992;Zemishlany and Thorne, 1991) and in participants with AD when compared to non-demented elderly participants (Sunderland et al, 1987), is consistent with the well-established age-and AD-related changes in a number of markers, including reductions in the size and number of cholinergic neurons in the NBM (McGeer et al, 1984;Whitehouse et al, 1982). Thus, the increased cognitive toxicity to trihexyphenidyl that we observed in participants with the APOE-e4 allele may reflect some form of decreased cholinergic function or reserve in this population.…”
Section: Discussionsupporting
confidence: 70%
“…Disruption of basal forebrain cholinergic pathways and consequent cortical cholinergic denervation is one of the hallmarks of AD, together with histopathological changes such as neurofibrilary tangles and senile plaques [20,21,37]. As expected, profound depletions in all cholinergic markers Fig.…”
supporting
confidence: 64%
“…3,[5][6][7][8][9]77 These neurons develop NFTs consisting of various forms of tau early in the disease process. 15,17 In the present study, we provide evidence for the onset of intraneuronal tau pathology before frank CBF neuron loss, which cor- relates with neuropathological criteria and tests of cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8][9] The viability of CBF neurons is dependent on the prototypic neurotrophic substance, nerve growth factor (NGF), 10 which is retrogradely transported to CBF neurons through a complex interaction of its two receptors, the high-affinity NGF-specific cell survival tyrosine kinase (trkA) and the putative cell death associated lowaffinity pan neurotrophin (p75 NTR ) receptor. 11,12 Previous studies have identified critical changes within the basocortical cholinergic system during the progression of AD, indicating a shift in the balance from pro-survival to apoptotic mechanisms, before frank cellular alteration, 13,14 which likely over time plays a mechanistic role in the CBF degeneration seen in AD.…”
mentioning
confidence: 99%